Serratacosa, a new genus of Lycosidae (Araneae) from the southern slopes of the Eastern Himalayas - Wang, Lu-Yu; Peng, Xian-Jin; Zhang, Zhi-Sheng (European Journal of Taxonomy, 2021)
A new wolf spider genus, Serratacosa gen. nov., is erected based on the type and new species, S. medogensis gen. et sp. nov. and two newly combined species, S. himalayensis (Gravely, 1924) (from Hogna Simon, 1885) and S. multidontata (Qu, Peng & Yin, 2010) (from Pardosa C.L. Koch, 1847). All of them are from the southern slopes of the Eastern Himalayas. Descriptions of the new genera and species, and a redescription of S. multidontata are provided together with digital images, illustrations and a distribution map.